Opto-VLSI-based tunable photonic RF filter - Xiao, F.; Juswardy, Budi; Alameh, K. (Springer, 2009)
In this paper, an Opto-Very-Large-Scale-Integrated (Opto-VLSI) based tunable photonic radio frequency (RF) filter structure is proposed and numerically simulated. The structure comprises a reconfigurable Opto-VLSI processor capable of arbitrarily steering optical beams of different wavelengths, a diffraction grating for wavelength division demultiplexing, and high-dispersion fibres for true-time delaying RF-modulated wavebands. The proposed structure has the ability to generate arbitrary wavebands and weights for realizing any RF filter responses. The proof-of-concept of the tunable photonic RF signal processor is also experimentally demonstrated by tuning its free-spectral range and altering its shape factor through optical beam steering. © 2010 Springer Science+Business Media, LLC.